Analisis Rasio Keuangan Dalam Memprediksi Profitabilitas Bank Syariah di Indonesia - Riska Sri Rahayu; Pani Akhiruddin Siregar (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to analyze influential and significant financial ratios in predicting the profitability of sharia bank in Indonesia. Financial ratios indicators using CAR, NPF and BOPO. As for profitability indicators using ROA. The research approach with quantitative methods is described by a multiple linear regression analysis model whose population is obtained from the Financial Ratios of Sharia Commercial Banks through the Sharia Indonesia Banking Statistics of the Financial Services Authority. The data is secondary in the form of monthly data for the period January 2017 to November 2022, so that a sample of 71 data was obtained for further analysis. Sampling techniques nonprobability by means of purposive sampling. The results of the study are as follows: (1) The estimation model shows an R2 value of 0,787 which represents the value of the coefficient of determination. This means that 78,70% of the dependen variable variation is able to be explained by the independen variables in this model. The remaining 21,30% is explained by other causes that are not included in the model; 2) The regression model on the independen variable simultaneously influence the dependen variable, so that the independen variable regression model can be used to predict the dependen variable; and (3) The results showed that CAR and NPF had an influential and significant analyzed financial ratios in predicting the ROA of sharia bank in Indonesia. The result showed that CAR and NPF had an influence in predicting the ROA of sharia bank in Indonesia. The results are as hypothesized. However, not on BOPO.